Vitamin D3 supplementation alleviates lipid accumulation, lipid metabolism disorder, and oxidative stress caused by a high-fat diet in juvenile black seabream (Acanthopagrus schlegelii) - Hao Cheng; Wenli Zhao; Yizhou Jiang; Yangguang Bao; Jiayun Zhu; Xinyan Zhi; Tingting Zhu; Peng Sun; Qicun Zhou; Min Jin (Aquaculture Reports)
This study investigates the potential of dietary vitamin D3 (VD3) to counteract the adverse physiological effects of a high-fat diet (HFD) in marine fish. Five isonitrogenous diets were formulated: a control diet (∼ 12 % lipid, Control), a HFD (∼ 18 % lipid, HFD), and HFDs supplemented with increasing levels of VD3 (6000, 12,000, and 18,000 IU/kg), referred to as HFD+6000VD3, HFD+12000VD3 and HFD+18000VD3, respectively. The actual VD3 contents in each diet were 10,400, 10,500, 18,100, 26,300 and 33,700 IU/kg, respectively. A total of 450 juvenile black seabreams (Acanthopagrus schlegelii) with an initial body weight of 5.39 ± 0.01 g were used in an 8-week feeding trial. Results showed that VD3 supplementation significantly up-regulated the expression level of cyp2r1, down-regulated the expression level of cyp24a1, and dramatically increased the expression level of vdrb, leading to higher 1,25(OH)2D3 levels in serum and liver (P < 0.05). Compared to the HFD, fish fed diets supplemented with VD3 exhibited reduced TG and TC levels in serum and liver, decreased expression levels of lipogenesis-related genes (aco3, fas, scd1, srebp-1c) and significantly enhanced the expression levels of lipolysis-related genes (hsl, pparα, lpl, atgl) (P < 0.05). Additionally, dietary VD3 supplementation significantly reduced serum AST and ALT activities (P < 0.05), and decreased the size and number of hepatic lipid droplets and vacuoles (P < 0.05). Furthermore, dietary VD3 inclusion decreased oxidative stress biomarkers, enhanced antioxidant enzyme transcription via the Nrf2 pathway, up-regulated antioxidant genes (cat, nrf2β, Cu-Zn sod), and reduced serum and liver MDA content, alleviating oxidative stress. In conclusion, dietary VD3 supplementation effectively mitigated HFD-induced hepatic fat deposition and lipid metabolism disorders in black seabream.